PERAN PEMERINTAH DALAM PENGEMBANGAN LEMBAGA PEMBIAYAAN DI SENTRA INDUSTRI BERBASIS EKONOMI KREATIF (Studi Kasus Industri Kuliner Kota Tangerang Selatan) - Harjawati, Tri (Sosio-Didaktika: Social Science Education Journal, 2018)
This article aims to illustrate the role of the government in the development of financing institutions in industrial centers based on creative economy. The method used is descriptive qualitative, using data collection techniques namely surveys, interviews, documentation, and literature. South Tangerang City. The results showed that the implementation of the creative economy in the area of South Tangerang City was already running but still not optimal. This is evidenced by 164 Industrial Culinary UMKM, only 12 UMKM can be considered superior and need attention to be developed. The role of the government in supporting the pattern of development of financial institutions in centers of creative economy-based industries in the area of South Tangerang City is limited to being a facilitator, namely assisting licensing and increasing land rights (Certificates) for creative industries. The role of the government in giving priority assistance and financing facilities in the creative economy industry has fulfilled the requirements, in the sense of only providing letters of recommendation for the creative industry.